The sambo encyclopedia : comprehensive throws, holds, and submission techniques - Scott, Steve, 1952- (YMAA Publication Center, Inc., 2019)
Sambo is considered one of the most effective, technically diverse, and dynamic modern fighting styles ever devised. Developed in the Soviet Union and based on Kodokan Judo and wrestling, sambo emphasizes utility over aesthetics. The end result is a fast paced and powerful system that excels in both throwing and ground fighting. Sambo techniques are being integrated into modern mixed martial arts with winning results. This book presents a systematic approach, presenting skills based on their function and utility in actual sport fighting, to how the sport of sambo is taught and practiced.--Publisher.